Mosque Fundraising Phenomenon (Mall-Amal) on Bangkalan Highway: Between Religious and Social Norms - Falah, M. Yasa Azmil; Krismono, Krismono; Hakim, Abdul (Potret Pemikiran, 2024)
The phenomenon of mosque fundraising on highways represents an established social practice in Indonesian society, particularly in Bangkalan Regency. This practice creates a unique dynamic between religious legitimacy and social norms that warrants comprehensive examination. This study aims to analyze the practice of mosque fundraising on Bangkalan Regency highways from the perspective of Islamic legal sociology, focusing on the interaction between religious and social norms that shape this practice. Employing a qualitative approach with field research methods, data were collected through in-depth interviews, observation, and documentation. The findings indicate that mosque fundraising practices on highways receive support from local religious leaders despite contradicting the Indonesian Ulema Council (MUI) fatwa. This support creates strong social acceptance, making it an integral part of local tradition that is difficult to modify. However, this practice raises challenges related to road user safety and trustworthy fund management. It can be concluded that the practice of mosque fundraising on Bangkalan Regency highways is formed through complex interactions between religious and social norms that mutually legitimize each other. Better management is needed to avoid negative impacts on society and increase awareness of public safety.